Free word association analysis of German laypeople’s perception of biodiversity and its loss - Eylering, Annike; Neufeld, Kerstin; Kottmann, Felix; Holt, Sebastian; Fiebelkorn, Florian (Frontiers in Psychology, 2023)
Due to the dramatic biodiversity crisis, it is crucial to understand how people perceive biodiversity. Knowledge of how thoughts are organized around this concept can identify which ideas are best to focus on biodiversity conservation information campaigns. The primary aim of the present study was to identify social representations of the German public regarding the concept of biodiversity and its loss using a free word association test. Furthermore, unique association networks were analyzed. For this purpose, data collection was performed in September 2021 in Germany using an online questionnaire to assess participants’ associations with the prompt “biodiversity” (n = 131) and “biodiversity loss” (n = 130). Additionally, we used the social network software Gephi to create biodiversity (loss) association networks. The five most commonly mentioned associations for biodiversity were “animal,” “plant,” “nature,” “human,” and “flower.” For biodiversity loss, the five most commonly mentioned associations were “species extinction,” “climate change,” “plant,” “insect,” and “bee.” Neither “land use change” nor “invasive species,” as key drivers of biodiversity loss, were present in social representations of the German public. A difference was observed in the total number of mentioned associations between biodiversity and biodiversity loss. For both, the associations “plant” and “animal” were related. However, participants associated specific taxa only with animals, such as “insects” and “birds.” For plants, no specific taxa were named. Based on the network analysis, the most commonly mentioned word pairs for biodiversity and biodiversity loss were “plant – animal” and “species loss – climate change,” respectively. Based on our statistical network analysis, these associations were identified as the most central associations with the greatest influence in the network. Thus, they had the most connections and the function of predicting the flow in the network. In sum, the public’s multifaceted views on biodiversity and its loss, as well as the aforementioned central associations, hold great potential to be utilized more for the communication and education of biodiversity conservation. In addition, our findings contribute to the scientific community’s understanding of social representations and perceptions of biodiversity and its loss.